Peranan Diakrisis di Dalam Kehidupan Spiritual Orang Percaya Menurut Bapa-bapa Padang Gurun - Hendi Hendi; Sarah Apriliana (DUNAMIS: Jurnal Teologi dan Pendidikan Kristiani, 2022)
Abstract. This article is an analysis of the words of the Desert Fathers regarding the important role of diacrisis in the spiritual life of believers contained in the book entitled: The Book of the Elders: “Sayings of Desert Fathers.” Diacrisis is a topic that is rarely discussed, even less studied by the Church today, so the purpose of this research is to get interesting facts about diacrisis experienced by people who have applied it in their spiritual life. The results of the analysis show that diacrisis plays an important role in the spiritual life of believers to lead to the perfection of living with God (Theosis).Abstrak. Artikel ini adalah sebuah analisis perkataan para Bapa Padang Gurun mengenai pentingnya peranan diakrisis di dalam kehidupan spiritual orang percaya yang terdapat dalam buku yang berjudul: “The Book of the Elders: Sayings of Desert Fathers.” Diakrisis ini merupakan topik yang cukup jarang dibahas bahkan kurang didalami oleh Gereja masa kini, sehingga tujuan dari penelitian ini adalah untuk mendapatkan fakta menarik tentang diakrisis yang dialami oleh orang-orang yang sudah menerapkannya di dalam kehidupan spiritual mereka. Hasil analisis menunjukkan bahwa diakrisis sangatlah berperan penting dalam kehidupan spiritual orang percaya untuk menuju pada kesempurnaan hidup bersama dengan Allah (Theosis).